NATIONAL IN GLOBAL TRADE PROCESSES ECONOMIC DEVELOPMENT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Within the framework of foreign trade policy, there are two main approaches - liberalization and protectionism, both of which affect different aspects of the national economy. Liberalization policy is mainly aimed at increasing economic activity by reducing customs barriers and creating a free trade environment. This approach stimulates globalization processes, facilitating the exchange of goods and services between countries, strengthening competitiveness and increasing economic efficiency. At the same time, liberalization creates new opportunities for national producers, as they gain access to international markets.